Stakeholders’ perception towards sustainable business locations of purpose-built office in Kuala Lumpur, Malaysia - Heng, Jia Yun (2019)
Purpose-built office (PBO) market in Malaysia has become more challenging in coming years since the sustainability has added new dimensions to the complexity in the location evaluation of PBO. Nevertheless, there is a lack of research in this country that studied the sustainable business locations of PBO based on the stakeholders’ perceptions. Therefore, this thesis aimed to develop a sustainable business location model to match the stakeholders’ perceptions on location of PBO in Golden Triangle Kuala Lumpur, Malaysia. For this purpose, ten main sustainable business location characteristics of PBO were identified. In developing the sustainable business location model of PBO, 8 out of 10 selected local expert panels who are property clients, valuers, property managers, estate agents and property consultants were involved in the content validation. For investigating the stakeholders’ perceptions towards sustainable business location characteristics of PBO, 190 pairwise comparison questionnaire sets were distributed and 157 questionnaires (82.63% response rate) were responded by the occupants of 19 selected PBOs. Analytic Network Process (ANP) technique was used to analyse the weight of dependence for sustainable business location characteristics of PBO based on the perceptions of PBO’s occupants. Hence, supermatrix approach was used to develop the location factor matrix for sustainable business locations of PBO. The research was successful in developing an ANP model and location factor matrix for sustainable business locations of PBO. The results has showed that the availability of transport options (C2), efficiency of property market (C5), access to public transportation and terminal (C8), and access to market (C9) characteristics have high limiting values for all the selected streets. Therefore, the results obtained in this research can provide new academic attainment for Malaysia in improving the development of purpose-built office market in Malaysia.